Causes and consequences of gender inequality - Amdadullah, . (2017)
Gender inequality is a persuasive global issue with huge cost and consequences. This thesis studies the causes and consequences of gender inequality in both developed and developing countries. First objective is to determine the impact of gender equality on income inequality. The second objective is to seek the impact of gender equality on education inequality. And the third objective is to determine the impact of institutional quality on gender equality. This study considers four aspects of gender equality; economic participation and opportunity, educational attainment, health and survival, and political empowerment. The study employs the Generalized Method of Moments (GMM) panel estimators developed for dynamic models of panel data, proposed by Arellano and Bond (1991) and Blundell and Bond, (1998) to estimate the models. First objective empirical results show significant effects of gender equality and its subindices on income distribution using panel data of 103 countries for the period of 2006- 13. The results show negative impacts of gender equality and its sub-indices on income distribution, suggesting that by increasing equality between males and females will result in lower income inequality. GDP per capita has nonlinear effect income inequality. Education attainment has a negative effect on income distribution, while higher inflation rate increases income inequality. The second objective is to investigate the impact of gender equality and its sub-indices on education inequality using panel data of 103 countries, over the period 2006–2014. Results reveal gender equality exerts a significant negative effect on education inequality, indicating that higher gender equality between males and females results in lower education inequality. GDP per capita, schooling and democracy have a negative and significant effect on education inequality. Conversely, unemployment, population density and dependency have a positive and significant impact on education distribution. The third objective uses the empirical results of panel data from 110 countries, for the period 2006–2014, show that the variable institutional quality has positive impact on gender equality and its sub-indices, suggesting that countries with improved institutional quality results higher level of gender equality. The empirical results confirm, GDP per capita has nonlinear significant effect on gender equality. Education attainment has positive impact gender equality. Likewise, fertility is found to have negative effect on gender equality. The analysis implies that improving gender equality effectively contributes to expanding equality in income and education. Improved institutions offer a significant contribution to gaining gender equality.